Ecomorfologia da ictiofauna de reservatórios do semiárido - Lima, Railla Maria Oliveira (2019)
Considered a highly diverse group, freshwater fish communities are greatly influenced by disturbances to aquatic environments. The northeastern semi-arid region, which was considered for a long time little diverse, supports rich communities and endemic species, according to current studies, but the region's environmental conditions such as low precipitation, temperature increase and habitat loss are factors that affect the region. maintenance and structuring of these communities. The association of these factors with human action, such as the construction of water storage dams, can affect the way these ecosystems function due to their dynamics. Since these artificial ecosystems are considered heterogeneous and complex, with chemical and physical multiformity, reservoir river connectivity will determine the conditions and integrity of these ecosystems, as well as predation as it is responsible for regulating prey through top-down control. Considering the peculiar characteristics of these ecosystems, studies have been directed to understand the structure of the ichthyological communities in the region, which are influenced by smaller scale abiotic elements and larger scale abiotic elements. In the environment, the availability of resources has great interference in exploitation and forms of interactions between species, since its abundant availability is exploited widely and when scarce, is exploited in a specialized way due to the intensification of predation and competition, This relationship allows the partitioning of resources and, consequently, coexistence, a mechanism that helps maintain the community and is associated with morphological, physiological and behavioral characteristics. Because of this association, ecomorphology points to morphology as the main responsible for species performance and this approach has been applied for the efficiency of inferring ecological aspects, especially in ichthyological communities, for the diversity of adaptations and ease of measuring morphological characteristics. Given the varied and complex conditions to which the ichthyological communities of the reservoirs are exposed, the study aims to analyze the morphological characteristics in order to characterize the life habits of ichthyological communities of three reservoirs of the Paraiban semiarid by applying the ecomorphological approach.